Meningkatkan Kesadaran Masyarakat Untuk Menghindari Transaksi Bisnis Yang Mengandung Unsur Riba di Kelurahan Harjosari 1 Kecamatan Medan Amplas - Batubara, Efira Andiyani; Nasution, Surayya Fadhilah; Tampubolon, Rhoni Ilham; Khairiyah, Ririn; Syafitri, Ahmaida; Hasibuan, Tasya Anisa (Yayasan Daarul Huda Kruengmane, 2024)
This service was carried out in Harjosari 1 Village, Medan Amplas District. The aim of this community service is to increase public awareness to avoid business transactions that contain elements of usury and to find out the level of success of the community service program for business transactions that contain elements of usury. The methods used in this community service activity are counseling, presentations and discussions. The results of the service show that firstly, the people of Harjosari 1 Subdistrict, Medan Amplas District, have an understanding of various business transactions, some already understand, some are still unsure, and some even don't understand. Second, to achieve the objectives of the community service activity program for the people of Harjosari 1 Subdistrict, Medan Amplas District, collaboration has been carried out between the community and service providers which is in accordance with the event rundown and predetermined time.